2013
DOI: 10.1071/wr13056
|View full text |Cite
|
Sign up to set email alerts
|

Body of evidence: forensic use of baseline health assessments to convict wildlife poachers

Abstract: Context. Given the immense impact of wildlife trade, disease and repatriations on populations, health assessments can provide powerful forensic material to help convict wildlife poachers and minimise risks of releasing unhealthy wildlife. Aims. We aimed to use reference ranges to assess the health of confiscated tortoises, to illustrate forensic application of these ranges, and to advance analyses for future applications. Methods. We used analyses of variance (ANOVA) and covariance (ANCOVA), and composite indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Geometric tortoises Psammobates geometricus are Critically Endangered (Hofmeyr and Baard 2015) because of a multitude of anthropogenic factors, including massive loss of habitat (c. 97%; Baard 1993Baard , 1995, an unnatural increase in fire frequency, predation by subsidised predators (e.g. Chacma baboons and Pied Crows), poaching (Henen et al 2013), and highly fragmented habitat resulting in small populations vulnerable to stochastic impacts such as fire (Baard 1995). The dire conservation status prompted establishment of reserves (Baard 1988) and research on the species' biology (Baard 1988(Baard , 1995Henen et al 2005Henen et al , 2013Hofmeyr et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometric tortoises Psammobates geometricus are Critically Endangered (Hofmeyr and Baard 2015) because of a multitude of anthropogenic factors, including massive loss of habitat (c. 97%; Baard 1993Baard , 1995, an unnatural increase in fire frequency, predation by subsidised predators (e.g. Chacma baboons and Pied Crows), poaching (Henen et al 2013), and highly fragmented habitat resulting in small populations vulnerable to stochastic impacts such as fire (Baard 1995). The dire conservation status prompted establishment of reserves (Baard 1988) and research on the species' biology (Baard 1988(Baard , 1995Henen et al 2005Henen et al , 2013Hofmeyr et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Chacma baboons and Pied Crows), poaching (Henen et al 2013), and highly fragmented habitat resulting in small populations vulnerable to stochastic impacts such as fire (Baard 1995). The dire conservation status prompted establishment of reserves (Baard 1988) and research on the species' biology (Baard 1988(Baard , 1995Henen et al 2005Henen et al , 2013Hofmeyr et al 2012). Our knowledge of P. geometricus habitat require ments and use is central to our ability to conserve them (Hofmeyr et al 2006(Hofmeyr et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Performing health evaluations on wildlife populations is being utilized more commonly by conservationists ( Mathews et al, 2006 ) and has become a proactive management approach that allows further conservation actions to be taken ( Madliger et al, 2017 ). For example, Henen, Hofmeyr & Baard (2013) found that confiscated adult tortoises showed poorer body condition and lower hematological values than wild ones, while Mathews et al (2006) found that water voles ( Arvicola terrestris ) with better body condition and higher hematological values had greater survival probability when reintroduced into the wild.…”
Section: Introductionmentioning
confidence: 99%
“…Retha's keen intellect and robust foundation in physiological ecology and integrative biology (e.g., Gericke et al 1978; Hofmeyr 1985; Schumann et al 2005) helped her tackle the challenge of southern Africa's rich tortoise diversity, with 14 native taxa, many endemic, and several endangered species (Fritz et al 2022). Fostered by collaborations with esteemed colleagues Ernst Baard, Gerald Kuchling, and Uwe Fritz, Retha authored or coauthored more than 60 peer-reviewed chelonian articles with topics ranging from morphometrics and physiology to reproductive ecology, behavior, forensics, phylogeography, phylogenetics, genetics, evolution, and conservation (e.g., Hofmeyr 2004, 2009; Hofmeyr et al 2005; Leuteritz and Hofmeyr 2007; Loehr et al 2007; Fritz et al 2011; Henen et al 2013; Rhodin et al 2018; Kuchling and Hofmeyr 2022). Retha and colleagues also published 12 International Union for the Conservation of Nature Red List assessments for sub-Saharan chelonians in 2015 and 2018, and 9 tortoise assessments for South Africa's 2014 Atlas and Red List Assessments for South African Reptiles .…”
mentioning
confidence: 99%